Diseño de un dispositivo terapéutico para niños desde los 18 meses a los 3 años que presentan displasia de cadera tratable con terapia física. - Martínez Novoa, Jonathan (Universidad Antonio Nariño, 2023)
At the moment in which a baby arrives at a home, a number of emotions and sensations between joy and nerves begin to arise. This is because beyond the increase in tears, smiles and daily tasks, there is an increase in responsibilities to guarantee a good general development of the baby.